Synchronous gallbladder squamous cell carcinoma and adenocarcinoma, both as primary tumors in one patient - Vahedi, Amir (Int J Surg Case Rep, 2018)
INTRODUCTION: Synchronous primary carcinomas of gallbladder are extremely rare. In this paper, we report a case of double primary carcinomas in gallbladder CASE REPORT: A 65 year old male was admitted to the hospital for surgical removal of gallbladder, which was diagnosed as cholecystitis in ultrasonography. Macroscopic examination disclosed a single whitish mass in gallbladder neck and another distinct mass in the fundus as wall thickening. Pathologic findings revealed squamous cell carcinoma of the neck and adenocarcinoma in the fundus. DISCUSSION: This study represents an example of misdiagnosis. Being cautious is mandatory in order to manage the patient properly. CONCLUSION: Synchronous primary carcinomas of gallbladder are rare. However this diagnosis should be taken into account in patients with cholecystitis features in order to seeking for the best surgical approach.